2021
DOI: 10.1149/1945-7111/ac1a52
|View full text |Cite
|
Sign up to set email alerts
|

DFT Electronic Properties and Synthesis Thermodynamics of Li x La1−x TiO3 Electrolytes for Li-Ion Batteries

Abstract: Lithium lanthanum titanate perovskites Li x La1−x TiO3 (LLTO) are promising solid-electrolytes for Li-ion batteries. We studied, in the Density-Functional-Theory framework, the thermodynamic stability and the electronic and magnetic properties of LLTO, as bulk materials and as thin slabs with (001) exposed surfaces. Results show that LaTiO3 (LTO) exhibits semiconductor behavior and G-type antiferromagnetic order (AFMG), whereas the TiO2-terminated LTO slab is a semiconductor with ferromagnetic (FM) order. Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…1a), as in previous reports. 16,50,51 In this work, only Li concentration x = 0.50 was considered, for two reasons: (i) to maintain the charge neutrality in the LLTO unit cell through the oxidation states presented by the Li + , La 3+ , Ti 4+ , and O 2− , taking care that the oxygen anions have completed their octet (i.e., eight electrons surround each O atom) and, consequently, their oxidation state 2-(this guarantees the energetic stability of LLTO perovskite); (ii) although the first requirement is met with x = 0.25 (for charge neutrality, the Ti cations have a mixed oxidation state of 3+ and 4+, as described in previous work, 16 where using the formal charges, the unit stoichiometric formula is Li + 0.25 La 3+ 0.75 Ti 3+ 0.5 Ti 4+ 0.5 O 2-3 or Li + La 3+ 3 Ti 3+ 2 Ti 4+ 2 O 2-12 by unit cell), the results showed that this LLTO compound is mechanically unstable. At zero GPa, the LLTO electrolyte presents a low-symmetry structure (triclinic) with 21 independent elastic stiffness coefficients after the geometric optimization process.…”
Section: Atomistic Structural Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…1a), as in previous reports. 16,50,51 In this work, only Li concentration x = 0.50 was considered, for two reasons: (i) to maintain the charge neutrality in the LLTO unit cell through the oxidation states presented by the Li + , La 3+ , Ti 4+ , and O 2− , taking care that the oxygen anions have completed their octet (i.e., eight electrons surround each O atom) and, consequently, their oxidation state 2-(this guarantees the energetic stability of LLTO perovskite); (ii) although the first requirement is met with x = 0.25 (for charge neutrality, the Ti cations have a mixed oxidation state of 3+ and 4+, as described in previous work, 16 where using the formal charges, the unit stoichiometric formula is Li + 0.25 La 3+ 0.75 Ti 3+ 0.5 Ti 4+ 0.5 O 2-3 or Li + La 3+ 3 Ti 3+ 2 Ti 4+ 2 O 2-12 by unit cell), the results showed that this LLTO compound is mechanically unstable. At zero GPa, the LLTO electrolyte presents a low-symmetry structure (triclinic) with 21 independent elastic stiffness coefficients after the geometric optimization process.…”
Section: Atomistic Structural Modelsmentioning
confidence: 99%
“…Using these requests, three LLTO configurations with nonequivalent structural, electronic, and elastic properties are found. 16 These LLTO structures are labeled as layered, columnar, and rocksalt bulk phases (LLTO-L, -C, and -RS, respectively). 53 In the LLTO-L, -C, and -RS structures, La 3+ are replaced by Li + at the sites (1, 2), (1,4), and (2, 4), respectively (Figs.…”
Section: Atomistic Structural Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…1−7 Therefore, safety is one of the most critical issues to be solved in developing large-scale applications for secondary lithium batteries with long cycling life. 7−12 Compared with the organic liquid electrolytes, ceramic electrolytes, such as NASICON, 13 perovskites, 14 garnet, 15 and sulfide-type ceramic/glass, 16 have the advantages of non-flammability, a high shear modulus (10−100 GPa) 17 against Li dendrite growth, and a high Li-ion transference number (t Li+ ≈ 1) at room temperature (R.T.). 18−21 Thus, all-solid-state lithium−metal batteries are recognized as the best candidate for next-generation energy storage by replacing the liquid electrolyte with a solid electrolyte (SE).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional commercial lithium-ion batteries usually use toxic, flammable, and corrosive liquid (organic) electrolytes, thereby bringing potential safety hazards, such as battery explosion and short circuits caused by thermal runaway behavior and uncontrolled growth of lithium dendrites. Therefore, safety is one of the most critical issues to be solved in developing large-scale applications for secondary lithium batteries with long cycling life. Compared with the organic liquid electrolytes, ceramic electrolytes, such as NASICON, perovskites, garnet, and sulfide-type ceramic/glass, have the advantages of non-flammability, a high shear modulus (10–100 GPa) against Li dendrite growth, and a high Li-ion transference number ( t Li+ ≈ 1) at room temperature (R.T.). Thus, all-solid-state lithium–metal batteries are recognized as the best candidate for next-generation energy storage by replacing the liquid electrolyte with a solid electrolyte (SE). Unfortunately, these SEs suffer from physicochemical stability issues, including high impedance at solid/solid interfaces and poor chemical stability in contact with Li metal, which hinder the application of solid-state batteries.…”
Section: Introductionmentioning
confidence: 99%